Determinative Surface-Wrinkling Microstructures on Polypyrrole Films by Laser Writing - Cong, Jianwen; Wang, Juanjuan; Xie, Jixun; Yang, Chengfeng; Zhao, Jingxin; Li, Lele; Cao, Yanping; Fery, Andreas; Feng, Xi-Qiao; Lu, Conghua (Langmuir, 2018)
We report a simple and efficient laser-writing strategy to fabricate hierarchical nested wrinkling microstructures on conductive polypyrrole (PPy) films, which enables us to develop advanced functional surfaces with diverse applications. The present strategy adopts the photothermal effect of PPy films to mimick the formation of hierarchical nested wrinkles observed in nature and design controlled microscale wrinkling patterns. Here, the PPy film is grown on a poly(dimethylsiloxane) (PDMS) substrate via oxidation polymerization of pyrrole in an acidic solution, accompanied by in situ self-wrinkling with wavelengths of two different scales (i.e., λ1 and λ2). Subsequent laser exposure of the PPy/PDMS bilayer induces a new surface wrinkling with a larger wavelength (i.e., λ3). Owing to the retention of the initial λ1 wrinkles, we obtain hierarchical nested wrinkles with the smaller λ1 wrinkles nested in the larger λ3 ones. Importantly, we realize the large-scale path-determinative fabrication of complex oriented wrinkling microstructures by controlling the relative motion between the bilayer and the laser. Combined with the induced changes in surface color, surface-wrinkling microstructures, and conductivity in the PPy films, the laser-writing strategy can find broad applications, for example, in modulation of surface wetting properties and fabrication of microcircuits, as demonstrated in this work.
CRIS-Team Scopus Importer:2022-04-14